Time-resolved X-ray photoelectron spectroscopy: ultrafast dynamics in CS2 probed at the S 2p edge - Gabalski, I; Allum, F; Seidu, I; Britton, M; Brenner, G; Bromberger, H; Brouard, M; Bucksbaum, PH; Burt, M; Cryan, JP; Driver, T; Ekanayake, N; et al. (American Chemical Society, 2023)
Recent developments in X-ray free-electron lasers have enabled a novel site-selective probe of coupled nuclear and electronic dynamics in photoexcited molecules, time-resolved X-ray photoelectron spectroscopy (TRXPS). We present results from a joint experimental and theoretical TRXPS study of the well-characterized ultraviolet photodissociation of CS2, a prototypical system for understanding non-adiabatic dynamics. These results demonstrate that the sulfur 2p binding energy is sensitive to changes in the nuclear structure following photoexcitation, which ultimately leads to dissociation into CS and S photoproducts. We are able to assign the main X-ray spectroscopic features to the CS and S products via comparison to a first-principles determination of the TRXPS based on ab initio multiple-spawning simulations. Our results demonstrate the use of TRXPS as a local probe of complex ultrafast photodissociation dynamics involving multimodal vibrational coupling, nonradiative transitions between electronic states, and multiple final product channels.